Makna dan Penghargaan Perempuan Nuaulu dalam Inisiasi Ritual Pinamou di Pulau Seram - Telfrin Tel Lasamahu; Izak Y. M. Lattu; Rama Tulus Pilakoanu (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2020)
This article aims to analyze the appreciation of women in the Pinamou ritual as an initiation ritual for women. The method used is a qualitative research method, with data acquisition through observation, interviews, audio-visual material, and literature studies. The study found in Pinamou ritual has an appreciation for the women who see in mythology about women. Then, it shows the figure of women as the successors of the life of a community and also as a source of blessing for both personal and community living in the community. The Pinamou ritual also has an affirmation of the initiation ritual that must carry out to reach the customary order in the community and become a place to look back at every meaning in the ritual performed.